Wage mobility, wage inequality, and tasks: Empirical evidence from Germany, 1984-2014 - Mustafa Coban (Julius Maximilian University of Würzburg, Chair of Economic Order and Social Policy, 2017)
Using the German Socio-Economic Panel and a newly available task database for Germany, the evolution of wage inequality, wage mobility, and the origins of wage mobility are studied. Since 2006 the increase in the German wage inequality has markedly slowed down, but there is a steady decline in wage mobility since 2000. In particular, workers in the services sector have ceteris paribus a significantly lower wage mobility than in the manufacturing sector. This result is mainly driven by the decrease of wage mobility in the health care and social services sector. Impact of a worker's unemployment spells and occupation on wage mobility has strengthened over the observation period. Between 2006 and 2013 wage and employment growth have been even polarized, but the routinezation hypothesis can only partially confirmed for wage mobility patterns. Workers who mainly perform manual tasks have a lower wage mobility over the observation period, but workers in cognitive routine occupations show a higher and increasing wage mobility over time compared to manual non-routine workers. In order to examine asymmetries in the effects of basic covariates on a worker's downward and upward wage mobility, multinomial logit estimations were applied. Except for the part-time workers, there are no obvious differences for the remaining covariates.
Keywords: J31; J24; 330; wage inequality; wage mobility; task approach; polarization hypothesis